Lesson study in initial teacher education to stimulate pedagogical content knowledge on the speed of sound - Conceição, Teresa (2020)
Background: Lesson Study is a collaborative model of teacher professional development that has received increasing international attention from many points of view. Objectives: This research aim to contribute to understand the effect of Lesson Study on the pedagogical content knowledge of the pre-service teachers on the speed of sound, at 8th grade. Design: This research is a qualitative and interpretative study. Setting and Participants: The participants were all preservice teachers attending the first year of a master program in teaching education in Physics and Chemistry. The Lesson Study comprises two cycles and took place over twelve sessions, in a total of 36 hours of work. Data collection and analysis: Data were collected from participant observation of all sessions using field notes and video recording, individual interviews and individual and group written reflections made by the pre-service teachers. Results: The results show that this Lesson Study stimulated the PCK in the speed of sound of the pre-service teachers because after diagnosing students’ previous knowledge they used this information to the lesson plan; because after the pre-service teachers established a relationship between the thunderstorm phenomenon and students’ difficulties they acknowledged that the phenomenon was not suitable for teaching the speed of sound at 8th grade; because after the pre-service teachers established a relationship between the nature of the topic and the students’ difficulties they understood the prior knowledge which is required for student learning the topic. Conclusions: Results encourage further research towards the generalised use of Lesson Study in initial teacher education.